Implementación de una aplicación PWA mediante el uso de API´S para personalizar los productos de decoración de interiores en la empresa ECODESIGN STUDIO - Añarumba Ulloa, Johnny Francisco (2022)
The present research work was executed in the company EcoDesign studio, located in the province of Pichincha, Quito, aims to develop a PWA by adapting the agile scrum methodology for the management of the production process and sale of furniture, in which the problem of an inadequate production process and sales management was identified, where sales were made manually in the establishment, this leads to a continuous loss of time. Therefore, for the development process of the application, information was collected by applying methodologies, different types of research tools such as: applied research, observation and field research. In addition, data collection techniques and instruments, such as interviews and surveys were used to obtain information on the problematic situation from primary sources. At the same time, agile practices were used for the implementation of the PWA application, including user stories, product backlog, prioritization and estimation, sprint planning, among others. Finally, software tools such as Python, PostgreSQL, Django Rest framework, Django, CSS, HTML, JQuery, JS, Bootstrap, Ubuntu, Lucidchart, Atom, Google Chrome were used. Achieving as a result to solve the inadequate process of sales management and production of furniture of the company EcoDesign studio, since the system allows to provide information of the company, contacts, make online purchases, registration of customer information, product management and payment method and thus concluded that it was developed an application focused on the management of production process and sales of furniture for the company EcoDesign studio.